Seasonal Progression of the Deposition of Black Carbon by Snowfall at Ny‐Ålesund, Spitsbergen. Issue 2 (17th January 2018) - Sinha, P. R.; Kondo, Y.; Goto‐Azuma, K.; Tsukagawa, Y.; Fukuda, K.; Koike, M.; Ohata, S.; Moteki, N.; Mori, T.; Oshima, N.; Førland, E. J.; Irwin, M.; et al.
Abstract: Deposition of black carbon (BC) aerosol in the Arctic lowers snow albedo, thus contributing to warming in the region. However, the processes and impacts associated with BC deposition are poorly understood because of the scarcity and uncertainties of measurements of BC in snow with adequate spatiotemporal resolution. We sampled snowpack at two sites (11 m and 300 m above sea level) at Ny‐Ålesund, Spitsbergen, in April 2013. We also collected falling snow near the surface with a windsock from September 2012 to April 2013. The size distribution of BC in snowpack and falling snow was measured using a single‐particle soot photometer combined with a characterized nebulizer. The BC size distributions did not show significant variations with depth in the snowpack, suggesting stable size distributions in falling snow. The BC number and mass concentrations ( C NBC and C MBC ) at the two sites agreed to within 19% and 10%, respectively, despite the sites' different snow water equivalent (SWE) loadings. This indicates the small influence of the amount of SWE (or precipitation) on these quantities. Average C NBC and C MBC in snowpack and falling snow at nearly the same locations agreed to within 5% and 16%, after small corrections for artifacts associated with the sampling of the falling snow. This comparison shows that the dry deposition was a small contributor to the total BC deposition. C MBC were highest (2.4 ± 3.0 μg L −1 ) in December–February and lowest (1.2 ± 1.2 μg L −1 ) in September–November. Key Points: The concentrations of black carbon measured in snowpack in Spitsbergen were somewhat insensitive to the snow water equivalent Concentrations of black carbon in falling snow and ambient air in midwinter were higher than those in fall on average The BC concentrations in snowpack measured by this study were lower than those previously reported by factors of 2–6